Analisis Jejaring Sosial Berdasarkan Topik Perbincangan “PPN 12 Persen” Di Sosial Media X - Yudatama, I Ketut (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
The policy to increase the Value Added Tax (VAT) rate to 12%, as mandated by Law Number 7 of 2021 concerning the Harmonization of Tax Regulations, has sparked diverse responses from the public, particularly on X (formerly Twitter) as a digital public discourse space. This study aims to analyze the social network structure and identify central actors within the public conversation regarding the